Involvement of oxytocin receptor deficiency in psychiatric disorders and behavioral abnormalities - Wei, Jinbao; Zheng, Huanrui; Li, Guokai; Chen, Zichun; Fang, Gengjing; Yan, Jianying (Frontiers in Cellular Neuroscience, 2023)
Oxytocin and its target receptor (Oxytocin receptor, OXTR) exert important roles in the regulation of complex social behaviors and cognition. The oxytocin/OXTR system in the brain could activate and transduce several intracellular signaling pathways to affect neuronal functions or responses, and then mediate physiological activities. The persistence and outcome of oxytocin activity in the brain are closely linked to the regulation, state, and expression of OXTR. Increasing evidence has shown that the genetic variations, epigenetic modification states, and expression of OXTR have been implicated in psychiatric disorders characterized by social deficits, especially in autism. Among these variations and modifications, OXTR gene methylation and polymorphism have been found in many patients with psychiatric disorders, and have been considered to be associated with those psychiatric disorders, behavioral abnormalities, and individual differences in response to social stimuli or others. Given the significance of these new findings, we in this review focus on the progress of OXTR’s functions, intrinsic mechanisms, and its correlations with psychiatric disorders or deficits in behaviors. We hope that this review can provide a deep insight into the study of OXTR-involved psychiatric disorders.